A Proposal for Cognitive Enhancement of the Elderly: An Alternative to Brain Training - Mogollón González, Eddy de Jesús (2014)
This paper is aimed at proposing an alternative for cognitive enhancement in the elderly, based on contributions and evidence presented by experts in the field.  Scientific positions for and against the use of brain training are analyzed.  The viability of this proposal is argued based on empirical evidence presented by theorists and researchers in the field of neuroscience, supported by modern brain scanning technologies.  It is concluded that, despite the natural vulnerability during aging, this proposal makes cognitive improvement possible as alternative brain training.